Dissertation Abstracts (Academy of Management Journal, 1964)
The article presents abstracts of two management-related studies. They include “The Structure of Organization,” by Ernest Sidney Lewis Goodwin and “An Analysis of Theoretical and Empirical Models of Capital Investment Decision Process,” by Michael P. Hottenstein.